Implementasi Knowledge Management di Lembaga Pendidikan ( Studi Kasus di Sekolah Dasar Islam Terpadu (SDIT) Khoiru Ummah Rejang Lebong ) - Enes, Utami Okta Ria; Rahman, Abdul; Apriani, Eka (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
In today's context, this era is often referred to as the Information Age or the Knowledge Era, characterized by the emergence of knowledge as a powerful force that can steer an organization or educational institution. Therefore, implementing knowledge management in educational institutions is crucial since they are places for acquiring knowledge. This research aims to comprehensively describe and analyze how knowledge management is applied in educational institutions, particularly in Khoiru Ummah Rejang Lebong Integrated Islamic Elementary School (SDIT). Using qualitative methodology, this research focuses on the case of the Khoiru Ummah Rejang Lebong Integrated Islamic Elementary School (SDIT). Using observation, interview and documentation techniques, data was obtained from various sources including school administrators, deputy head of curriculum, deputy head of student affairs, deputy head of Islamic Personal Development (BPI), deputy head of T2Q, and several Integrated Islamic Elementary School (SDIT) teachers. ) Khoiru Ummah. Rejang Lebong. The research results show that the application of knowledge management at the Khoiru Ummah Rejang Lebong Integrated Islamic Elementary School (SDIT) includes various procedures, such as information discovery, capture, sharing, and application. This helps improve education-related policies, focusing on important aspects such as long-term planning, resource management, education quality and accessibility.